Effectiveness of a Modified 2-Rescuer Cardiopulmonary Resuscitation Technique Using a Bag-Mask for Less Experienced Health Care Providers: A Randomised Controlled Simulation Study. Issue 1 (January 2015) - Shim, Hw; Park, So; Lee, Yh; Yoo, Yb; Hong, Dy; Baek, Kj; Lee, Kr
Objective: To determine if a modified 2-rescuer cardiopulmonary resuscitation (CPR) method, in which the first rescuer performs chest compressions and squeezes the bag-mask during pauses in compression, and the second resuscitator uses 2 hands to provide an open airway, is useful for less experienced health-care providers (HCPs). Methods: In this randomised control simulation study using a manikin, 82 less experienced HCPs were enrolled. After training on the conventional 2-rescuer CPR method (CM) (n=42) and the modified 2-rescuer CPR method (MM) (n=42), each participant performed 2-rescuer CPR for 5 cycles using their respective methods. All data were recorded in a personal computer and then analysed. Results: The MM group generated a higher mean tidal volume (TV) (675.2 mL versus 320.0 mL for the CM) and higher median numbers of ventilation with the correct TV over 5 cycles (7 versus 3 breaths for the CM) (all p<0.001). However, there was no significant difference in the quality of chest compression and related interruption between the CM and MM groups. However, relatively higher median number of ventilations with large TV (2 versus 0 breaths for the CM) and higher median number of ventilations (3 versus 0 breaths for the CM) over 5 cycles were delivered in the MM group (all p<0.001). Conclusions: Modified 2-rescuer CPR method (the first rescuer performs chest compressions and squeezes the bag-mask during pauses in compression, and the second resuscitator uses 2 hands to provide an open airway) can be useful as an alternative CPR method and is preferable to the conventional 2-rescuer CPR method for less experienced health-care providers. (Hong Kong j.emerg.med. 2015;22:23-30)